P133 AN ANALYSIS OF SURGICAL OUTCOMES IN IBD PATIENTS TREATED WITH AND WITHOUT BIOLOGIC THERAPY. (18th January 2018) - Gudsoorkar, Vineet; Ibarra, Sergio; Gonzalez-Almada, Alberto; Oglat, Ayah; Koduru, Pramoda; Abraham, Bincy; Haas, Eric
Abstract: Background: Treatment options for inflammatory bowel disease (IBD) have expended tremendously in the past two decades. Biologics have now been increasingly used early in the course of therapy with the goal of inducing remission and thus delaying or avoiding the need for surgery. In spite of these advances, approximately 1/3rd of the patients with ulcerative colitis (UC) and 70% of those with Crohn's disease (CD) undergo surgery over their lifetime. Comparative data of different biologics regarding surgical outcomes are relatively sparse outside of the clinical trials. Method: Fifty-one patients (34 CD, 17 UC) undergoing IBD-related surgery from 4/2015-4/2017 were retrospectively studied. 48 patients were classified into "No biologic", "Anti-TNF" (patients on infliximab/adalimumab/certolizumab) and "Vedolizumab" groups based on their biologic therapy at the time of surgery. Pertinent data were obtained, including the history of biologic use. Surgical outcomes were measured as 30-day readmission rate, complications and need for post-operative blood transfusion. T-test and Chi-square test were used for analysis. Results: In the "No biologics" group, 9/12 were biologic-naïve and 3 had been exposed to one biologic in the past. In the anti-TNF group, 4/20 had been exposed to single biologic and 3/20 had been exposed to 2 biologics in the past. In the vedolizumab group, 12/16 patients had been exposed to 2 or more biologics before vedolizumab. Comparing these three groups of patients, no statistically significant difference was noted across these groups with regards to surgical complication rate. Conclusion: No significant differences in surgical outcomes were noted in patients preoperatively not on biologics, those who were on anti-TNFs and on vedolizumab, an anti-integrin biologic. The patients on vedolizumab were exposed to more number of biologics in the past, likely indicating a more complex disease.